OXA-484, an OXA-48-Type Carbapenem-Hydrolyzing Class D β-Lactamase From Escherichia coli - Sommer, Julian; Gerbracht, Kristina M.; Krause, Felix F.; Wild, Florian; Tietgen, Manuela; Riedel-Christ, Sara; Sattler, Janko; Hamprecht, Axel; Kempf, Volkhard A. J.; Göttig, Stephan (Frontiers in Microbiology, 2021)
OXA-48-like carbapenemases are among the most frequent carbapenemases in Gram-negative Enterobacterales worldwide with the highest prevalence in the Middle East, North Africa and Europe. Here, we investigated the so far uncharacterized carbapenemase OXA-484 from a clinical E. coli isolate belonging to the high-risk clone ST410 regarding antibiotic resistance pattern, horizontal gene transfer (HGT) and genetic support. OXA-484 differs by the amino acid substitution 214G compared to the most closely related variants OXA-181 (214R) and OXA-232 (214S). BlaOXA-484 was encoded on a self-transmissible 51.5 kb IncX3 plasmid (pOXA-484) showing high sequence similarity with plasmids harboring blaOXA-181. Intraspecies and intergenus HGT of pOXA 484 to different recipients occurred at low frequencies of 1.4×10-7 to 2.1×10-6. OXA-484 increased MIC of temocillin and carbapenems similar to OXA-232 and OXA-244, but lower compared with OXA-48 and OXA-181. Hence, OXA-484 combines properties of OXA-181-like plasmid support and transferability as well as β-lactamase activity of OXA-232.